2019
DOI: 10.3906/vet-1905-82
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on some minerals, metabolites and enzyme activities in the serum of trained Arabian horses

Abstract: The exercise-induced variations of some biochemical parameters including calcium (Ca), phosphorous (P), iron (Fe), copper (Cu), manganese (Mn), selenium (Se), zinc (Zn), sodium (Na), potassium (K), chlorine (Cl), glucose, urea, creatinine, lactate dehydrogenase (LDH), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and creatine kinase (CK) were assessed in the serum of 25 Arabian horses. Blood samples were taken from the jugular vein 3 different times: before exercise, 5 h after exercise, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, the age of the mare and her parity number should be considered when comparing the results, as previous studies have indicated variations in the concentrations of both Cu and Zn depending on the mare's age [48,49]. This variability may help to explain the high degree of variance observed within the groups in this study.…”
Section: Limitationsmentioning
confidence: 82%
“…Furthermore, the age of the mare and her parity number should be considered when comparing the results, as previous studies have indicated variations in the concentrations of both Cu and Zn depending on the mare's age [48,49]. This variability may help to explain the high degree of variance observed within the groups in this study.…”
Section: Limitationsmentioning
confidence: 82%
“…Platelet activation is a physiological response of the hemostatic system to physical activity.The intensive horse training leads to increased platelet aggregation and that hypercoagulability in horses with pulmonary hemorrhages is associated with significant thrombocytosis after the race (Giordano et al 2010). The significant hypocalcemia found in draft horses after rest was confirmed by Pourmohammad et al (2019). Hypocalcemia after exercise can probably be caused in the following ways: binding calcium to the troponin molecule, lactates, phosphates, and plasma albumins, and restoring stored calcium ions within the sarcoplasmic reticulum (Vervuert et al 2002;Dummont et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, results in terms of elemental levels in the blood may be subject to error, since active homeostatic mechanisms compensate for levels in the blood at the expense of reserves in the body [ 8 ]. Many authors point out that the advantage of the hair material is also due to the fact that its mineral composition documents the supply of various elements over a longer time profile than is the case, for example, with blood, where changes can occur in a daily profile [ 9 , 10 ]. Hair is a good matrix for the initial assessment of elemental levels [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%